Intervention for Reducing Maternal Mental Health Problems in The Golden Period: Systematic Review - Farisya Nurliana Fatin; Farida Fitriana; Gatut Hardianto (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Data from World Health Organization informs that 10-16% of pregnant women and 13-20% of postpartum women have mental health problems worldwide. The most vulnerable time in this problem is when women experience it in the first 1000 days of life or the golden period. This issue has been untreated because of the gap between needs and service availability. This study aims to analyze the intervention for reducing maternal mental health problems during the golden period, especially can provide by the midwife as a health professional who is more accessible to the mother.Methods: Systematic review took articles from PubMed, Science Direct, Epistemonikos, and Google Scholar. Literature searching found 235 articles in 2021 that were analyzed using the PRISMA diagram.Result: Maternal mental health problem occurs due to the transition phase of the parent which is making a change of role and responsibility. It can provide negative effects on mother and child health. The articles have shown non-pharmacology interventions that have a different effect. Even, cognitive behavioral therapy shows a dominant effect in all studies that can use as single or combine therapy depending on the mother's condition. The midwife has also responsible to do early detection and should be taken training to facilitate this service for the mother.Conclusion: Maternal mental health during the golden period is crucial, especially for optimizing the child's development by the mother. Although the interventions have variated result, it is still beneficial for the mother.